2007
DOI: 10.1002/elps.200600747
|View full text |Cite
|
Sign up to set email alerts
|

Two‐chiral component microemulsion EKC – chiral surfactant and chiral oil. Part 2: Diethyl tartrate

Abstract: In this second study on dual-chirality microemulsions containing a chiral surfactant and a chiral oil, a less hydrophobic and lower interfacial tension chiral oil, diethyl tartrate, is employed (Part 1, Foley, J. P. et al.., Electrophoresis, DOI: 10.1002/elps.200600551). Six stereochemical combinations of dodecoxycarbonylvaline (DDCV: R, S, or racemic, 2.00% w/v), racemic 2-hexanol (1.65% v/v), and diethyl tartrate (D, L, or racemic, 0.88% v/v) were examined as pseudostationary phases (PSPs) for the enantiosep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…One noteworthy improvement in resolution was for pseudoephedrine, which dramatically increased between 1.0 Â and 1.5 Â phase ratio compositions. Previous studies indicated that in some cases, two chiral component systems would fare better in efficiencies than those systems with one chiral component [11]. The aggregates containing 1.65% racemic 2-hexanol generally had lower efficiencies as compared with similar systems with S-2-hexanol.…”
Section: Resultsmentioning
confidence: 88%
“…One noteworthy improvement in resolution was for pseudoephedrine, which dramatically increased between 1.0 Â and 1.5 Â phase ratio compositions. Previous studies indicated that in some cases, two chiral component systems would fare better in efficiencies than those systems with one chiral component [11]. The aggregates containing 1.65% racemic 2-hexanol generally had lower efficiencies as compared with similar systems with S-2-hexanol.…”
Section: Resultsmentioning
confidence: 88%
“…the chiral surfactant R-and S-dodecoxycarbonylvaline (DDCV) [11]. Kahle and Foley have completed extensive studies involving the effects of single, dual and triple chiral component ME systems [11,[54][55][56][57]. A summary of their findings are covered in previous reviews [1,57].…”
Section: Advances In Chiral Separations Utilising Meekcmentioning
confidence: 97%
“…In previous studies by Kahle and Foley [11,[54][55][56]58] it was suggested that the chiral surfactant (R-and S-DDCV) may have contained impurities, which would have impacted on the enantioselectivity, resolution, efficiency and migration of enantiomeric ephedrine compounds. Recently, Kojtari and Foley [59] investigated the purity of R-and S-DDCV and its impact on the enantioseparation of chiral ephedrine and pseudoephedrine.…”
Section: Effect Of Me Component Purity On Chiral Separationmentioning
confidence: 99%
“…Atenolol enantiomers were partially separated using diethyl tartrate microemulsions. With a three-chiral component microemulsion, an increase in enantioresolution of MT (Rs 1.59, 1.85, 1.95, with one, two, three-chiral component, respectively) was achieved while a decrease in efficiency was observed for atenolol (N 126100, 103400, 87400, with one, two, three-chiral component, respectively) [111][112][113].…”
Section: Mekc and Meekcmentioning
confidence: 99%